Development of the Energy Sector in the Display of Key Exchange Indices - Petrukhnov, O. V.; Negliad, A. V.; Lyashenko, V. (IJAMSR, 2023)
Economic development makes it necessary to provide a sufficient amount of resources and sources of their receipt. Among such objects, a special place is occupied by those that allow you to receive energy. This type of resource is important for t he implementation of all types of activities and the functioning of any types of business entities, households. Obt aining this resource is associated with the use of minerals or the possibility of using renewable sources. In the first case, it is important to know the availability of minerals, which is generally determined by the dynamics of the respective prices. These prices are formed as a result of trading on the stock exchange and are determined by the dynamics of the respective stock indices. We consider various exch ange indicators. The dynamics of the relationship of such indices is also considered. The paper pre sents a series of graphs and charts that allow you to understand the progress of the study. The results obtained make it possible to assess the dynamics of the develo pment of the global energy sector.
Keywords: energy; wavelet analysis